Revitalisasi Tafsir Ekologi pada Kandungan Surat Al-A'raf [7] Ayat 56-58 dalam Rencana Penanaman Pohon Trembesi di Lingkungan UIN Walisongo Semarang - Eka Mulyo Yunus; Andika Andika; Ahmad Yani; Muria Khusnun Nisa; Hasyim Muhammad (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Climate change caused by emission substances is a real problem. Carbon emissions produced by vehicles, households can erode the climate from time to time. One way to overcome this is by planting tamarind trees.This study aims to analyze the ecological interpretation of Surah Al-A'raf verses 56-58 in the plan to plant trembesi trees at UIN Walisongo Semarang. This study uses a qualitative approach through technical methods according to Miles and Huberman, namely data reduction, data presentation, and drawing conclusions and field observations by direct observation. The results of this study discuss environmental studies, science and religion in one Trembesi tree environment in accordance with Al-A'raf verses 56-58. This study concluded that the Trembesi tree, if calculated by experts, could absorb 28.5 tons of CO2 gas annually (canopy diameter 15m). So that it becomes an innovation that will be developed at UIN Walisongo Semarang. This research is recommended to commentators, biologists and students as well as government agencies so that the use of Trembesi trees can continue to be developed